2018
DOI: 10.15517/ma.v29i1.27550
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del desarrollo testicular y medidas morfométricas en ovinos de pelo colombiano

Abstract: The sheep body measurements are useful indicators of type and function that allow improving the selection. Biometric studies have shown in sheep a relationship between these measures with some productive variables. The main purpose of this study was to evaluate the testicular development and their relationship with morphometric parameters on Colombian hairy sheep of Sampués, Sucre, Colombia. Weaned males (n=12) born between February and April of 2014 were used, and the following measures were taken every twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
0
0
2
Order By: Relevance
“…According to the literature for small ruminants and cattle, the physical examination and reproductive evaluation include the external genitalia: testicles, foreskin, glans; in the present study, normal values were found to what was established for the species (Espitia-Pacheco et al, 2018). However, some bodily characteristics such as the general condition of the animals: dull and bristly hair, watery eyes, presence of mucus in the nasal cavity, dirt in the hairs of the foreskin can alter the physical and reproductive health of the animals (De Celis et al, 1996).…”
Section: Resultssupporting
confidence: 74%
“…According to the literature for small ruminants and cattle, the physical examination and reproductive evaluation include the external genitalia: testicles, foreskin, glans; in the present study, normal values were found to what was established for the species (Espitia-Pacheco et al, 2018). However, some bodily characteristics such as the general condition of the animals: dull and bristly hair, watery eyes, presence of mucus in the nasal cavity, dirt in the hairs of the foreskin can alter the physical and reproductive health of the animals (De Celis et al, 1996).…”
Section: Resultssupporting
confidence: 74%
“…La circunferencia escrotal es de los principales parámetros que se toman en cuenta para la selección de sementales, puesto que se sabe que el tamaño testicular se correlaciona con la capacidad reproductiva de los machos (Espitia-Pacheco et al, 2018), siendo un parámetro que posee de alta a moderada heredabilidad (Barrozo et al, 2012). También es una variable que se considera para evaluar el desarrollo reproductivo, la espermatogénesis y las características seminales (Gallego-Calvo et al, 2018).…”
Section: Discussionunclassified
“…Segundo a classificação de a consistência testicular indicou uma textura firme, porém elástica. Os animais Dorper do presente estudo aos 12 meses de vida apresentaram uma maior CE e um menor CT em comparação aos ovinos colombianos avaliados na mesma idade por EspitiaPacheco et al (2018), que obtiveram 28.3 ± 1.5 cm de CE e 11.0 ± 0.7 cm de CT. A LT dos ovinos estudados foi maior que o observado por Camela et al, (2019), porém, a medida de CT foi menor comparado ao observado por esses autores, onde em Dorper adultos, entre 1224 meses apresentaram as seguintes medidas testiculares: 4.9 ± 1.2 cm de LG; 9.7 ± 0.3 cm de CT. Os autores relataram que a puberdade estava associada às alterações na biometria testicular.…”
Section: Registros De Medidas Corporais E Testicularesunclassified